Analysis of WhatsApp Mod User Awareness Information Security with Static Analysis Methods and Quantitative Methods - Banu Santoso; Muhammad Abdul Ghofur; Jeki Kuswanto (Akademi Angkatan Udara, 2021)
Increasing technological developments make the use of technology in the world alsoincrease and have a good or bad impact on the security of information that exists in cyberspace, this existing information security can be spread and accessed by irresponsible people by taking advantage of security gaps from every information media that exist in cyberspace, one of the gaps that allows for crimes to occur by utilizing unofficial applications where the application offers more attractive features so that users want to use the application. Applications that are widely used include the type of social chat network, where in this case the theme of WhatsApp mod users is raised, where the WhatsApp mod offers several features that do not exist in the official WhatsApp application on the Android platform. This can be one of the gaps where application development is not carried out officially, where data and information disseminated through the WhatsApp mod communication media cannot be guaranteed. Therefore, this research is expected to provide a percentage value related to the level of awareness of WhatsApp users which can be used as learning related to existing information security by paying attention to the results of static analysis related to security holes in the WhatsApp mod application.